Pengaruh Relation Ship Marketing Terhadap Loyalitas Konsumen Pada Cafe Corner Juanda Di Samarinda - Agus Budiman; Sri Mintarti; Tetra Hidayati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this research is to know the influence Relation Ship Against Consumen Loyalty Marketing At Cafe Corner Juanda in Samarinda.The theoretical foundation of marketing management used to use multiple linear regression analysis with 73 sample.The function regresi calculation result is Y = 1,250+0,204 X1 + 0,483 X2, these function has the meaning if an increase in the quality of functional benefits and sosial benefits will lead to an increase consumer loyalty on The Cafe Corner Juanda in Samarinda , the reggresion coefficient values because all variabels market positively.The value of F hitung F tabel and significance Î± = 0,05 which means together variabel of functional benefits and sosial benefits have significance influence to wards consumer Loyalty on Cafe Corner Juanda in Samarinda, Then accepted research hypothesis.Partially functional benefits have variabels showed significance effect againts the dominant Consumer Loyalty and Cafe Corner Juanda in Samarinda indicated by the value of the calculation result t table other variabels that mean the hypothesis advanced functional benefits of influential variabels supposedly dominant againts Consumer Loyalty Cafe Corner Juanda in Samarinda , accepted.Keywords : pyschologycal Factors, The Charactheristics of Individual Consumer Decisions